Phytochemical Profile, Antioxidant Activity, and Brine Shrimp Lethality Test of Thyrsostachys siamensis (Siamese Bamboo) Leaf Extracts - Muhamad Aditya Hidayah; Indah Ayudia; Gerda Pintoko Tunjungsari; Retno Aliyatul Fikroh; Alfandi Ahmad (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Cancer and oxidative-stress–related disorders continue to rise globally, driving interest in plant-based antioxidants with concurrent cytotoxic potential. This study aimed to characterize the phytochemical profile, antioxidant activity, and brine shrimp (Artemia salina) lethality of Thyrsostachys siamensis (Siamese bamboo) leaf extracts obtained with solvents of increasing polarity (n-hexane, chloroform, acetone, ethyl acetate, methanol, ethanol, and water). Ethanol appears as the most effective solvent for T. siamensis, combining a solid extraction yield (7.78%) with the richest phytochemical profile (positive for alkaloids, flavonoids, saponins, tannins, and phenolics). This broad chemical recovery corresponds to the strongest bioactivity, shown by its lowest IC50 (91.48 ± 0.12 µg/mL) and LC50 (80.78 ± 0.62 µg/mL). Acetone (6.42%) and ethyl acetate (5.11%) offer moderate yields and selective enrichment of semi-polar constituents, reflected in intermediate IC50 values (144–150 µg/mL) and LC50 values (273–350 µg/mL). In contrast, hexane despite providing the highest mass recovery (11.34%) contains mainly non-phenolic components and shows weak biological activity (IC50 200.52 ± 0.38 µg/mL, LC50 620.06 ± 0.76 µg/mL). Chloroform, with limited phytochemical content, yields the poorest performance (IC50 238.30 ± 1.56 µg/mL, LC50 926.40 ± 4.27 µg/mL).